Untersuchungen an Eisbohrkernen von Alpengletschern - Stauffer, B.; Schotterer, U. (Geographica Helvetica, 1985)
Cold alpine glaciers are archives of climatic Parameters. Core drilling in alpine glaciers allows to collect ice samples of ages up to 1000 years. First results from analyses of an ice core from Colle Gnifetti (Swiss Alps) show already interesting results. Frequent occurring dust bands contain mainly dust from the Sahara and are therefore characteristic for precipitations transported with subtropic air masses. An increase of the acidity of the precipitations starting at the beginning of our Century is most probably an anthropogenic effect. For the upper 10 m of the ice core, S04- and N03- concentrations have also been measured.